Zileuton, a new efficient and safe systemic anti-acne drug - Zouboulis, Christos C (Landes Bioscience, 2009)
Tissue inflammation is a major component of the acne process. Leukotriene B(4) (LTB(4)) is considered to be a major player in the development of tissue inflammation. Synthesis of LTB(4) is controlled by the enzyme 5-lipoxygenase. Since Zileuton blocks the activity of 5-lipoxygenase, experimental and clinical studies have been conducted to test mode of function, as well as efficacy and safety of this compound in the treatment of acne vulgaris. Human SZ95 sebocytes and inflammatory cells in vitro express the enzymes of the leukotriene pathway at mRNA and protein levels and enzymes involved in the biosynthesis of LTB(4) are activated in sebaceous glands of acne lesions. Pre-treatment of SZ95 sebocytes with Zileuton partially prevented short-term arachidonic acid-induced effects, such as induction of LTB(4), increase of neutral lipid content and stimulation of interlekin-6 release. Long-term treatment with Zileuton directly reduced the content of neutral lipids and interleukin-6 release from SZ95 seb ocytes. PPAR mRNA levels were not regulated by Zileuton. In a first pilot clinical study with 10 patients with papulopustular acne Zileuton 4 × 600 mg/d p.o. for 3 months decreased the acne severity index in a time-dependent manner being 41% of the initial score at week 12 (p < 0.05). This was mostly due to a decrease of the number of inflammatory lesions of 29% (p < 0.01). In addition, total sebum lipids significantly decreased (35%, p < 0.05) and the pro-inflammatory free fatty acids (22%) and lipoperoxides (26%) were markedly diminished in patients’ sebum under treatment. The magnitude of clinical improvement strongly correlated with the reduction of total sebum lipids (p = 0.0009, r(2) = 0.81) and free fatty acids (p = 0.0003, r(2) = 0.82). In a further study, a 40-year-old female with mild disseminated sebaceous gland hyperplasia and seborrhea, responded with normalization of the casual skin surface lipids and similar reduction of facial sebum synthesis under treatment with Zileuton over 2weeks and—after a wash-out phase—low-dose isotretinoin (10 mg/2nd d) over 5 weeks. These data are in agreement with a phase II multicenter, clinical study in 101 patients with mild to moderate inflammatory facial acne conducted in the US, which showed a significant efficacy of Zileuton in a subset of patients with moderate acne, whereas those patients treated with Zileuton showed a significant mean decrease in inflammatory lesions compared to the placebo group. In all clinical studies, Zileuton was found to be safe and well tolerated.